Neovascularization in Advanced Atherosclerosis - A Histomorphometric Study - Paul, Veena; Mary Priya Paul, Christina; Kuruvilla, Sarah (International Journal of Medical Research and Review, 2016)
Introduction: Neovascularization is an important component of advanced atherosclerosis which leads to plaque vulnerability and rupture. This is an endarterectomy study where neovascularization is quantified in 50 advanced atherosclerotic plaques by using IHC stain and measuring the positivity by histomorphometry, simultaneously assessing lipid pool area and fibrous cap thickness (average and minimum), also by histomorphometry. The values were compared across different AHA types and also probable vulnerable plaques were identified. Materials & Methods: Three heart specimens obtained at autopsy from subjects who died of RTA showed evidence of coronary artery disease on post-mortem coronary angiogram. Coronary endarterectomy was done from these specimens and was made into tissue blocks for histological study. On H& E sections the plaques were classified by AHA typing and 50 advanced atherosclerotic plaques were chosen for this study. To assess neovascularization, the IHC stain CD34 was used and the percentage area of positivity was later measured using histomorphometry. The lipid pool area in the plaques and the fibrous cap thickness were also measured using histomorphometry. Results: In our study, 47 out of 50 advanced lesions showed neovascularization although the difference in their amounts between AHA Type IV and V was not statistically significant. On measuring lipid pool area and fibrous cap thickness, we found 4 of the 50 plaques to be probable vulnerable plaques as they had a combination of a large lipid pool (>40% of the plaque area) and a thin fibrous cap (<65μ) in addition to revascularization. Conclusion: This study showed that neovascularization was seen in most of the advanced atherosclerotic plaques and together with some other features like large lipid pool and thin fibrous cap, it can potentially make a plaque vulnerable to rupture. The understanding of role of neovascularization in plaque rupture has led to the trial of antiangiogenic therapy to prevent plaque progression.